Health observatories in iran. - A Rashidian; B Damari; B Larijani; A Vosoogh Moghadda; S Alikhani; K Shadpour; A Khosravi (Tehran University of Medical Sciences, 2013)
The Islamic Republic of Iran, in her 20 year vision by the year 2025, is a developed country with the first economic, scientific and technological status in the region, with revolutionary and Islamic identity, inspiring Islamic world, as well as effective and constructive interaction in international relations. Enjoying health, welfare, food security, social security, equal opportunities, fair income distribution, strong family structure; to be away from poverty, corruption, and discrimination; and benefiting desirable living environment are also considered out of characteristics of Iranian society in that year. Strategic leadership towards perceived vision in each setting requires restrictive, complete and timely information. According to constitution of National Institute for Health Researches, law of the Fifth Development Plan of the country and characteristics of health policy making, necessity of designing a Health Observatory System (HOS) was felt. Some Principles for designing such system were formulated by taking following steps: reviewing experience in other countries, having local history of the HOS in mind, superior documents, analysis of current production and management of health information, taking the possibilities to run a HOS into account. Based on these principles, the protocol of HOS was outlined in 3 different stages of opinion poll of informed experts responsible for production on management of information, by using questionnaires and Focus Group Discussions. The protocol includes executive regulations, the list of health indicators, vocabulary and a calendar for periodic studies of the community health situation.